2019
DOI: 10.1112/s0010437x19007139
|View full text |Cite
|
Sign up to set email alerts
|

Local-global principles in circle packings

Abstract: We generalize work of Bourgain-Kontorovich [6] and Zhang [32], proving an almost local-to-global property for the curvatures of certain circle packings, to a large class of Kleinian groups. Specifically, we associate in a natural way an infinite family of integral packings of circles to any Kleinian group A ≤ PSL 2 (K) satisfying certain conditions, where K is an imaginary quadratic field, and show that the curvatures of the circles in any such packing satisfy an almost local-to-global principle. A key ingredi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…The tangency spinors are spinors for the 3-dimensional space with Minkowski quadratic form of signature (1,2). It has been a somewhat metaphorical use of the term native to mathematical physics of (1+3)-dimensional spacetime for objects in 2-dimensional geometry.…”
Section: Unification: Pauli Spinors From Tangency Spinorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tangency spinors are spinors for the 3-dimensional space with Minkowski quadratic form of signature (1,2). It has been a somewhat metaphorical use of the term native to mathematical physics of (1+3)-dimensional spacetime for objects in 2-dimensional geometry.…”
Section: Unification: Pauli Spinors From Tangency Spinorsmentioning
confidence: 99%
“…And now some basic notions organized in a form that should be easy to consult. For more on the subject see [1,2,3,5,12,15,16,17,20].…”
Section: Introductionmentioning
confidence: 99%
“…The Bourgain-Kontorovich result has recently been generalized by Fuchs, Stange, and Zhang. Remark that [8] restricts attention to M, N ∈ PSL 2 (K), not PGL 2 (K) as stated above. Communication with the second-and third-named authors confirmed that their proof still applies.…”
Section: 3mentioning
confidence: 99%
“…Consequences of Theorem 1.1 include a restriction on possible intersection angles within certain subarrangements called bugs from [12] (Corollary 4.3), a criterion for determining superintegrality (Definition 4.4, Proposition 4.6), and a geometric connection between S D and the local-global principle for curvatures in an integral circle packing (Theorem 4.11 and Corollary 4.13). Regarding the last result, the relative position of a circle packing in S D can give a sufficient condition for applying a theorem of Fuchs, Stange, and Zhang [8], which states that curvatures in certain packings have asymptotic density 1 among integers that pass a set of local obstructions. A circle packing that satisfies our sufficient condition is displayed in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…In all these cases, there is a corresponding local-global conjecture, just as for the Apollonian circle packing. This conjecture is open for all such circle packings, but there are known density one results like the theorem of Bourgain and Kontorovich-see, for example, [FSZ17]. For n = 2, there is the generalization of the Apollonian circle packing to spheres due to Soddy [Sod36]; additionally, Dias [Dia14] and Nakamura [Nak14] independently constructed the orthoplicial sphere packing.…”
Section: Introductionmentioning
confidence: 99%